RELASI AGAMA DAN KEBANGSAAN DI INDONESIA - Uan Abdul Hanan (STAINU Purworejo, 2020)
Indonesia is a large nation and has a long history in determining the direction of the nation and state. The direction of that direction rests on cultural values ​​and religious values ​​that have grown in the midst of society for a long time. Efforts to realize civil society become very necessary, where the discourse arises from the non-believers who are not classified as modernists. What moves, how is the essence of the sunnah wal pilgrims and nationality as well as their relationsTo discuss that, the authors explore the writings about the nature and relations between the two with a philosophical approach, especially on the ontology side, the analysis uses deductive analysis to find the nature and inductive to find the relations between the two.The essence of the Sunnah Wal Jamaah Expert is a method of thinking (manhaj) which is constantly transformed to find contextualization in answering the problem, while the nature of nationalism refers to human beings who share common ideals and form the state as a tool of struggle. In the context of Indonesia, the relationship between the two is reflected in the four pillars of Indonesian nationhood, namely: Pancasila, the 1945 Constitution of the Republic of Indonesia, Unity in Diversity and the Unitary State of the Republic of Indonesia